The effectiveness of promotional effort towards Nestle beverages / Mohd Hazwan Md Kharmani - Md Kharmani, Mohd Hazwan (Faculty of Business and Management, 2009)
Industrial Training (MKT 661) is a core subject under Faculty of Business Management. The main objective of this course is to expose students to the 'real' working environment and get acquainted with the organization structure, business operations and administrative functions. I have completed my industrial training at Malacca State Development Corporation (PKNM) started from 01st Jun 2009 until 19th October 2009. I have been assigned to join the Corporate Unit. During the training period, I did lots of assignments given by the company’s staff and supervisor. The most assignment that I received is the documentation. I have to analyze, study and draft letter to other unit or government companies based on the standard official format. Other than letter, I also learned how to write memos, make agreement, proposal and etc. However, I enjoyed doing the task because from the task I learned how to manage and handle the meeting and event. At the same time, I experienced with the real project such as organized the “sukan rakyat” and “Karnival Beli Barangan Buatan Malaysia 2009”. Overall, instead of gaining lots of knowledge and experienced I also felt very happy and enjoyed for my industrial training. The State Economic Development Corporation (PKNM) own many subsidiaries company in Malacca and one of them is PM Multilink Sdn. Bhd.. In this study, PM Multilink Sdn. Bhd. face several problems especially in ensuring either the promotion mix used by them will enhance level of customer’s awareness toward the products and services their provided. The objective of the research is to examine whether the promotional mix done by PM Multilink Sdn. Bhd. are effective and to identify the most effective promotion mix which may enhance customers awareness towards products and services offered by PM Multilink Sdn. Bhd. as well as to identify the level of customer’s awareness towards products and services offered by PM Multilink Sdn. Bhd.